Investigating the Effect of Normative Pressure on the Level of Adjustment between Ahvaz Youth and Their Parents with an Emphasis on Generation Gap - Daryoush Rezapour; mohammad bagher koopai (توسعه اجتماعی, 2020)
A main factor affecting social and cultural developments in the contemporary era is “generation gap”, which is itself a result of social changes. This study was done to investigate the effect of normative pressure on the level of adjustment between youth and their parents with an emphasis on the generation gap. This is a survey research, using a questionnaire for collecting data. The statistical population includes all 18-30 years old Ahvazi youth, out of whom 400 people were selected as the sample size using Lin table. The sampling method was multi-stage random sampling. SPSS was used to analyze the data. The results showed there was a significant relationship among the level of normative pressure, using mass media, age and education with the adjustment of the youth with their parent with an emphasis on generation gap. However, there was no significant relationship between employment status and youth gender with the dependent variable. Step-wise regression analysis showed that the variable of normative pressure and the youth’ use of mass media were the most influential factors on the level of generation gap and inconsistency between youth and their parents, respectively